A cluster of atypical resistance genes in soybean confers broad-spectrum antiviral activity. Issue 4 (3rd November 2021) - Yan, Ting; Zhou, Zikai; Wang, Ru; Bao, Duran; Li, Shanshan; Li, Aoga; Yu, Ruonan; Wuriyanghan, Hada
Abstract: Soybean mosaic virus (SMV) is a severe soybean ( Glycine max ) pathogen. Here we characterize a soybean S MV r esistance c luster (SRC) that comprises five resistance ( R ) genes. SRC1 encodes a TIR-NBS (Toll/interleukin-1 receptor and nucleotide-binding site) protein, SRC4 and SRC6 encode TIR proteins with a short EFh (EF hand) domain, while SRC7 and SRC8 encode TNX (TIR-NBS-X) proteins with a non-canonical BSP (basic secretory protein) domain at their C-termini. We mainly studied SRC7, which contains a non-canonical BSP domain and gave full resistance to SMV. SRC7 possessed broad-spectrum antiviral activity toward several plant viruses including SMV, plum pox virus (PPV), potato virus Y (PVY) and tobacco mosaic virus (TMV). The TIR domain alone was both necessary and sufficient for SRC7 immune signaling, while the NBS domain enhanced its activity. Nuclear oligomerization via the interactions of both TIR and NBS domains was essential for SRC7 function. SRC7 expression was transcriptionally inducible by SMV infection and SA (salicylic acid) treatment, and SA was required for SRC7 triggered virus resistance. SRC7 expression was post-transcriptionally regulated by miR1510a and miR2109, and the SRC7 -miR1510a/miR2109 regulatory network appeared to contribute to SMV-soybean interactions in both resistant and susceptible soybean cultivars. In summary, we report a soybean R gene cluster centered by SRC7 that is regulated at both transcriptional and post-transcriptional levels, possesses a yet uncharacterized BSP domain, and has broad-spectrum antiviral activities. The SRC cluster is special as it harbors several functional R genes encoding atypical TNL type R proteins, highlighting its importance in SMV-soybean interaction and plant immunity.